An inverse model for optimisation of laser heat flux distributions in an automated laser tape placement process for carbon-fibre/PEEK. (September 2016) - Stokes-Griffin, C.M.; Compston, P.
Abstract: High power diode lasers have enabled higher placement rates to be achieved in automated tape placement (ATP) of thermoplastic-based composite materials. Laser ATP heads in published literature employ homogeneous linear or rectangular laser spots, however a variety of solutions are available to produce customised irradiance profiles. No efforts to date have investigated what a more ideal heat flux profile would be for laser ATP in terms of length and distribution. This paper describes a method to determine the required laser heat flux profiles to achieve desired heating zone temperature profiles by means of an inverse thermal model. A bonding model was implemented to assess the performance of various heating zone temperature profiles for placement at 400 mm/s. Short beam strengths from experimental trials (Stokes-Griffin and Compston, 2015) were used to validate the bonding model. A two-stepped heating profile was found to provide a good balance of increased strength with a small increase in power requirement.